2020
DOI: 10.1002/andp.201900578
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Two‐Photon Three‐Degrees‐of‐Freedom Hyper‐Parallel Controlled Phase Flip Gate Through Cavity‐Assisted Interactions

Abstract: Hyper-parallel quantum information processing is a promising and beneficial research field. Herein, a method to implement a hyper-parallel controlled-phase-flip (hyper-CPF) gate for frequency-, spatial-, and time-bin-encoded qubits by coupling flying photons to trapped nitrogen vacancy (NV) defect centers is presented. The scheme, which differs from their conventional parallel counterparts, is specifically advantageous in decreasing against the dissipate noise, increasing the quantum channel capacity, and redu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 129 publications
0
8
0
Order By: Relevance
“…The key step of our multiple-DOF MDI-QKD protocol is the HBSA. Such HBSA protocol was also used in realizing the high-capacity quantum secure direct communication [72] and constructing the two-photon three DOFs hyper-parallel controlled phase-flip gate [73]. However, the complete HBSA protocol adopted in our MDI-QKD protocol requires the cross-Kerr nonlinearity technique, which is still a challenge under current experimental condition.…”
Section: Discussionmentioning
confidence: 99%
“…The key step of our multiple-DOF MDI-QKD protocol is the HBSA. Such HBSA protocol was also used in realizing the high-capacity quantum secure direct communication [72] and constructing the two-photon three DOFs hyper-parallel controlled phase-flip gate [73]. However, the complete HBSA protocol adopted in our MDI-QKD protocol requires the cross-Kerr nonlinearity technique, which is still a challenge under current experimental condition.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperparallel quantum gates have attracted much attention in recent years due to their excellent properties. Up to now, some interesting protocols for implementing hyperparallel quantum gates have been proposed via photon-matter platforms [31][32][33][34][35][36], and the inevitable incomplete and imperfect photon-matter interactions are usually not taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Lu et al [42] demonstrated a frequency-bin based CNOT gate. And in 2020, Wei et al [36] presented a hyperparallel CPF gate utilizing the frequency DOF together with the spatial-mode and time-bin DOFs of a two-photon system. Frequency-based entanglements were employed by Zeng and Zhu [43] to complete hyper-Bell analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, different from polarization photons, the frequency, spatial, and time-bin photons are immune to the decoherence effects and the bit-flip errors in optical fibers. Moreover, hyperentangled states can be used to complete some tasks which are impossible to achieve with the single DOF, such as entanglement witness, 14) linear-optical Bell-state analysis, 15) and one-way quantum com-and hyper-Toffoli gates [25][26][27][28] have been proposed.…”
mentioning
confidence: 99%